2020
DOI: 10.20473/joints.v9i2.2020.63-70
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Arthritis of the Ankle Mimicking Synovitis in Child - A Case Report

Abstract: Background: Extrapulmonary Tuberculosis is approximately 10% of all tuberculosis (TB) cases, and the musculoskeletal system’s involvement was only 2-4. The incidence of ankle TB was found to be less than 2% of all musculoskeletal TB. The rare occurrence, uncommon site, non-specific symptoms, lack of awareness frequently causes diagnosis difficulties.Case Report: A 2,5-year-old child came to the hospital with the main complaints of swelling and pain on the left ankle since one year ago. She was diagnosed with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…There is lack of literature regarding diagnostic tools in TB of small joints, including the midfoot joints. Many authors have reported that in any tubercular osteomyelitis, bone sclerosis or PVNS may be seen in the early course of disease [18] , [19] , [20] . Ruling out other conditions is required, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…There is lack of literature regarding diagnostic tools in TB of small joints, including the midfoot joints. Many authors have reported that in any tubercular osteomyelitis, bone sclerosis or PVNS may be seen in the early course of disease [18] , [19] , [20] . Ruling out other conditions is required, i.e.…”
Section: Discussionmentioning
confidence: 99%